Effectiveness of mobile mindfulness training on stress, burnout, and work engagement of office workers: protocol for a randomized controlled trial - Lee, Seung Il; Yoon, Seok In; Song, Geum Ju; Park, Hui Yeong; Chung, Sun Yong; Kim, Jong Woo (Frontiers in Public Health, 2025)
BackgroundWork stress has a detrimental impact on individual health and corporate efficiency and productivity. Mindfulness reduces workers’ stress and burnout and increases work engagement and performance. Smartphone-based interventions could be an alternative to provide customized training without geographical or economic constraints. This study aims to investigate whether mobile mindfulness training (MMT) improves office workers’ stress, burnout, and work engagement.MethodsThis study is a two-arm randomized controlled trial. In total, 114 office workers will be randomly assigned to one of two groups: an experimental group and a control group. The experimental group will undergo MMT, following both daily and event guidelines, for the first 4 weeks. In contrast, the control group will not receive any intervention for the first 4 weeks. During the next 4 weeks, the control group will undergo MMT for ethical reasons. Assessments will be conducted at baseline, post-intervention (fourth week), and follow-up (eighth week). The outcomes are burnout, work engagement, perceived stress, mindfulness, and vitality.DiscussionThis study will serve as a basis for evaluating the effectiveness of MMT on stress, burnout, and work engagement of office workers.Ethics and disseminationThis study was approved by the Institutional Review Board of Kyung-Hee University [KHSIRB-24-063(RA)]. The results will be disseminated through peer-reviewed publications.Clinical trial registrationIdentifier [KCT0009458]. https://cris.nih.go.kr/cris/search/detailSearch.do?seq=26951&status=5&seq_group=26951&search_page=M